1984
DOI: 10.1073/pnas.81.2.461
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic calcium regulates epidermal growth factor endocytosis in rat pancreas and cultured fibroblasts.

Abstract: Cholecystokinin octapeptide (CCK8), the COOH-terminal moiety of cholecystokinin (CCK), exerted a rapid inhibitory effect on total cell-associated 125I-labeled epidermal growth factor As in the case of a number of other polypeptide hormones, high concentrations of EGF decrease the number of EGF receptors on the cell surface through a process called "downregulation." EGF binding and internalization are also modulated by a variety of nonphysiological agents. Thus, binding of EGF to its receptor is altered by ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 32 publications
(24 reference statements)
2
20
0
Order By: Relevance
“…Interactions between EGF and CCK, homologues ofTGFa and gastrin, respectively, have been well studied on pancreatic exocrine cells. CCK decreases EGF receptor binding by stimulating intracellular C kinase activity, which inhibits internalization of receptor bound EGF (28,29). Although the metaplastic ductules contain numerous insulin-positive cells, the islet mass of the TGFa transgenic mice was not increased over controls.…”
Section: Discussionmentioning
confidence: 93%
“…Interactions between EGF and CCK, homologues ofTGFa and gastrin, respectively, have been well studied on pancreatic exocrine cells. CCK decreases EGF receptor binding by stimulating intracellular C kinase activity, which inhibits internalization of receptor bound EGF (28,29). Although the metaplastic ductules contain numerous insulin-positive cells, the islet mass of the TGFa transgenic mice was not increased over controls.…”
Section: Discussionmentioning
confidence: 93%
“…Ca2l has been suggested to be involved in association of normally soluble protein kinase C with plasma membranes (37,38). In addition, Ca2l has been shown to act synergistically in altering EGF internalization (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a variety of secretagogues, including bombesin, inhibit 125I-EGF association to pancreatic acinar cells by increasing cytosolic Ca 2÷ in the cells (28,31,46). The following paper (37) reports that bombesin and bombesinrelated peptides induce Ca 2÷ mobilization from intracellular stores and increase cytosolic Ca 2÷ concentration in 3T3 cells (37).…”
Section: Role Of Lncreased Cytosolic Ca 2+ and Protein Kinase C In Mementioning
confidence: 96%
“…It has also been reported that bombesin reduces the association of ~:5I-EGF to 3T3 cells (4) and to pancreatic acinar cells, an effect apparently mediated by an increase in the cytosolic Ca 2+ concentration (28,31,46). In the course of our studies concerning the early events elicited by peptides of the bombesin family in quiescent Swiss 3T3 cells, we examined the effect of these peptides on the binding and internalization of ~25I-EGF into Swiss 3T3 cells, and the parts played by protein kinase C and an increase in cytosolic Ca 2+ in mediating the inhibition of t2SI-EGF association caused by bombesin.…”
mentioning
confidence: 87%